Knowledge and Practices on Antibiotic Use and Antibiotic Resistance Among Smallholder Pig Farmers in Timor-Leste - Ting, Shawn; Pereira, Abrao; Davis, Steven; Vong da Silva, Paulo Gabriel; Alves, Amalia; Dos Santos, Cristibela; Toribio, Jenny-Ann L. M. L.; Morais, Olavio; da Costa Jong, Joanita Bendita; Barnes, Tamsin S. (Frontiers in Veterinary Science, 2022)
Antibiotic resistance is an emerging global health threat which is linked to the overuse and misuse of antibiotics. This study was conducted to understand the knowledge and practices of smallholder pig farmers on antibiotic use and resistance in Timor-Leste. A cross-sectional study using a structured face-to-face interview was conducted in 3 municipalities. The interview was piloted and implemented in the local Tetun language. This study found that knowledge of antibiotics was very poor as only 12.7% (95% CI: 6.3 – 23.9) of farmers reported knowing what antibiotics were, and of these only one was able to correctly explain how an antibiotic worked. None of the farmers knew about antibiotic resistance and were able to explain the concept correctly. After the definition of antibiotic was explained to the farmer, only 3.6% (95% CI: 0.8 – 14.9) reported that their pigs had ever received antibiotics, and the majority of farmers whose pigs had not received antibiotics reported the lack of access to veterinary services. When used, antibiotics were only used for treatment with no reported use for disease prevention or growth promotion. None of the commonly used antibiotics were critically important antimicrobials. Compliance with withdrawal periods was not routinely followed. There is a need to improve access to government veterinary services for farmers in Timor-Leste, while addressing identified knowledge gaps on antibiotics and promoting prudent use practices. The findings from this study serve as baseline information to inform future interventions.